Dental restoration composite material with self-healing function and preparation method thereof
Patent Information
- Application Number
- CN202611129680.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
然而,现有技术存在以下显著不足:自愈合触发方式多为被动式,依赖裂纹扩展产生的机械力,无法实现精准、按需的靶向修复;愈合剂的长期稳定性不足,易在储存以及加工过程中提前反应;修复体通常为单一均质材料,与天然牙齿的仿生多层结构不匹配,导致力学性能和美学效果不佳;缺乏针对修复完成后服役期间微裂纹的、可临床操作的标准化维护与效果评估方法
[0021]本发明的有益效果之一为:通过构建基托层、牙本质层、釉质层的仿生多层结构,并严格控制各层树脂的溶解度参数差值及界面化学键合工艺,保障了修复体整体的力学完整性、层间结合强度及长期服役稳定性;
Smart Images

Figure CN122997967A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of dental restorative materials technology, specifically to a biomimetic multilayer dental restorative composite material with self-healing function and its preparation method. Background Technology
[0002] Dental restorations are prone to developing microcracks on their surface and inside due to long-term complex oral stresses such as chewing, abrasion, temperature changes, and chemical environments such as saliva and microorganisms. The propagation of these microcracks is a major cause of restoration fracture, secondary caries, and restoration failure. Once a traditional restoration develops cracks, it can only be replaced, increasing the patient's suffering and financial burden.
[0003] To extend the lifespan of dental restorations, the concept of self-healing materials has been introduced into the dental field. Current technologies typically employ embedding healing agent microcapsules and hollow fibers within a resin matrix. When cracks develop, external force breaks the microcapsule walls, releasing the healing agent to achieve repair. However, existing technologies have the following significant drawbacks: self-healing is mostly triggered passively, relying on the mechanical forces generated by crack propagation, making precise, on-demand targeted repair impossible; the long-term stability of the healing agent is insufficient, easily reacting prematurely during storage and processing; restorations are usually made of a single homogeneous material, incompatible with the biomimetic multi-layered structure of natural teeth, resulting in poor mechanical properties and aesthetics; and there is a lack of clinically applicable standardized maintenance and effectiveness evaluation methods for microcracks that may develop during the post-restoration period.
[0004] Therefore, developing a dental restorative composite material with long-lasting latency, a biomimetic multilayer structure, and the ability to precisely target and trigger self-healing through external energy, along with its corresponding clinical maintenance solutions, is of significant clinical importance and application value. Summary of the Invention
[0005] Purpose of the invention The primary objective of this invention is to provide a dental restorative composite material with self-healing function. This material has an integrated biomimetic multilayer structure containing core-shell-shell composite microcapsules with long-lasting latency, and can achieve precise and targeted self-healing repair of microcracks through external ultrasonic energy.
[0006] Another objective of this invention is to provide a method for preparing the above-mentioned dental restorative composite material. This method uses microfluidic technology to precisely control the microcapsule structure and employs layered casting and gradient curing processes to ensure the chemical bonding of the multilayer interfaces and the integrity of the overall structure, thereby achieving controllability and consistency of material properties.
[0007] Technical solution In a first aspect, the present invention provides a dental restorative composite material with self-healing function, which is an integrated biomimetic multilayer structure, comprising a base layer, a dentin layer and an enamel layer bonded together by a chemical bonding interface.
[0008] The base layer resin is a methyl methacrylate-ethyl methacrylate copolymer with a molar ratio of 7:3, which is modified by KH-570 silanization to give it excellent biocompatibility and support strength.
[0009] The dentin and enamel layers were constructed using Bis-GMA / TEGDMA resin systems in a 1:1 ratio and UDMA / TEGDMA resin systems in a 2:1 ratio, respectively, with the difference in solubility parameters of the resin monomers in each layer ≤ 1.5 (J / cm³). 3 The 0.5 ratio ensures excellent interlayer chemical compatibility, enabling the formation of high-strength chemical bonds through interfacial copolymerization.
[0010] The dentin layer and enamel layer contain self-healing functional units with volume fractions of 25±5% and 15±5%, respectively.
[0011] The composite microcapsules have an overall particle size of 80±20 μm and a three-layer structure consisting of a core, a shell, and a hull. The inner core is a liquid TEGDMA repair monomer, accounting for 50±5% of the volume.
[0012] The intermediate trigger layer, comprising 10±2% of the volume, is a solid-state isolation mixture of BPO and DMPT. Both are physically adsorbed onto the surface of porous silica nanoparticles modified with KH-550, with a particle size of 50-200 nm and a porosity of 40±10%. Aging tests showed a contact reaction rate of ≤5% after 6 months in artificial saliva at 37℃, ensuring long-lasting latency.
[0013] The outer shell is made of PMMA with a weight-average molecular weight of 150,000 ± 20,000 and inorganic nano-damping filler. The dentin layer microcapsule shell filler is uniformly distributed, with a content of 5 ± 1%, an average thickness of 1.8 ± 0.1 μm, and a circumferential tensile strength of not less than 15 MPa. The enamel layer microcapsule shell has a gradient structure in which the filler content linearly increases from 5% to 15% from the inside out, with an average thickness of 2.5 ± 0.1 μm.
[0014] The rupture of the outer shell is triggered by a combined thermal and mechanical mechanism. The rupture energy density thresholds for the dentin and enamel microcapsules are 0.8 ± 0.1 W / cm², respectively. 2 and 1.3±0.1 W / cm 2When the stress concentration factor in the crack region is ≥1.5, under the action of 40-60 kHz ultrasound, the local thermal effect and the synergistic effect of the periodic alternating stress can induce targeted fatigue cracking of the shell in the crack region within about 60 seconds, release the repair monomer and mix it with BPO / DMPT in the intermediate trigger layer, induce room temperature polymerization, and achieve self-healing.
[0015] Furthermore, the fracture threshold (Eth) and the average shell thickness (d) satisfy the formula Eth = k·d within the range d∈[1.8μm, 2.5μm]. 2 For a silica-filled uniform shell, k = 0.24 ± 0.02 W·μm -2 / cm 2 For gradient-walled shells, k = 0.21 ± 0.02 W·μm -2 / cm 2 The k-value of the silicon carbide filler system is approximately 0.22 ± 0.02 W·μm. -2 / cm 2 The gradient structure, as verified by finite element simulation, can reduce the maximum stress concentration factor by approximately 20%.
[0016] Furthermore, all relevant performance parameters were obtained by testing under the condition that the microcapsules were uniformly dispersed in artificial saliva at 37°C. Different contents of silica and silicon carbide fillers corresponded to different power-temperature rise relationships and rupture thresholds.
[0017] Furthermore, the chemically bonded interface is formed by copolymerization at 60°C with the addition of KH-570 and TBPB initiators. The molar participation ratio of the interfacial comonomer is ≥40%, there is no cross-quenching between TBPB and the photoinitiation system, and the interlaminar shear strength is not less than 15-22 MPa.
[0018] Secondly, the present invention provides a method for preparing the above-mentioned dental restorative composite material, comprising: S1. Preparation of composite microcapsules: S101. Synthesize PMMA prepolymer with controlled molecular weight; S102. Using sequential microfluidics, the flow rate ratio of the core phase, intermediate phase, and shell phase is controlled at 1:2:5. Microcapsules are prepared by adjusting the hydraulic diameter of the channels and the superposition of the shell phase gradient.
[0019] S2. Layered preparation and casting: Prepare each layer of slurry, controlling the layer thickness to ≤500μm, and verify that the penetration depth of 470nm blue light is ≥500μm. Cast the slurry into the mold in the order of base layer, dentin layer, and enamel layer, and perform blue light layered pre-curing immediately after each layer is cast.
[0020] S3. Gradient hot-pressing curing: In an isostatic pressing cylinder, the pressure is increased to 8±0.1 MPa at 0.5 MPa / min, then the temperature is increased to 85℃ at 5℃ / min and held for 90 minutes, and finally the temperature is reduced to room temperature at 5℃ / min. This process suppresses the deformation rate of microcapsules at the curing temperature by more than 50% and ensures that the residual stress of the final resin matrix is ≤3 MPa.
[0021] One of the beneficial effects of this invention is that by constructing a biomimetic multilayer structure of base layer, dentin layer and enamel layer, and strictly controlling the difference in solubility parameters of resin in each layer and the interfacial chemical bonding process, the overall mechanical integrity, interlayer bonding strength and long-term service stability of the restoration are guaranteed. The second beneficial effect of this invention is that by using an intermediate triggering layer structure with porous silica nanoparticles as the isolation carrier, BPO and DMPT are physically isolated, and through surface modification and process control, the self-healing functional unit achieves a latency stability of up to 6 months in artificial saliva at 37°C, solving the problem of premature activation and functional failure in traditional systems. The third beneficial effect of this invention is that by designing a PMMA shell with a gradient and uniform filler distribution, and establishing a quantitative relationship formula for wall thickness and rupture threshold, Eth = k·d 2 This enables precise control of the rupture threshold of microcapsules with different functional layers, thereby matching their different mechanical and crack propagation behaviors; The fourth beneficial effect of this invention is that, by revealing and quantifying the thermo-mechanical synergistic triggering mechanism of local temperature rise reducing PMMA fatigue strength and ultrasonic alternating stress, it achieves the desired effect at specific ultrasonic parameters of 40-60 kHz and 0.5-2.0 W / cm². 2 The targeted and efficient triggering of self-healing microcapsules in microcrack areas improves the accuracy and efficiency of self-healing. The fifth beneficial effect of this invention is that by adopting sequential microfluidic technology and a specific shell-phase laminar flow superposition process, precise preparation of the core, shell, and shell structure of composite microcapsules is achieved, ensuring the consistency of the structure and performance of the functional units. The sixth beneficial effect of the present invention is that by using the preparation process of layered casting, layered pre-curing and gradient hot pressing curing, and controlling the residual stress ≤3MPa, the integrity of the microcapsules and the perfect fusion of the interfaces of each layer in the integrated multilayer structure are ensured during the molding process, and the problems of internal stress and interface defects in the molding of complex structures are solved. The seventh beneficial effect of this invention is that by providing a clinical maintenance method that includes specific parameters, repeatable and standardized repair of microcracks in the prosthesis and objective effect verification are achieved, thereby improving the reliability and convenience of the clinical application of this technology. Attached Figure Description
[0022] Figure 1 This is a flowchart illustrating the preparation method of a dental restorative composite material with self-healing function according to the present invention. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions and as recommended by the manufacturer.
[0024] Example 1: This embodiment provides a dental restorative composite material with self-healing function and its standard preparation method, aiming to demonstrate its integrated biomimetic multilayer structure and the realization of key components. The key components include a base layer, a dentin layer, a resin system for the enamel layer, and two composite microcapsules for the dentin layer and the enamel layer, respectively, and follow the core process steps of this invention.
[0025] Materials and proportions: Base layer slurry: Resin matrix: A binary copolymer of methyl methacrylate (MMA) and ethyl methacrylate (EMA) in a molar ratio of 7:3. This copolymer was grafted with γ-methacryloyloxypropyltrimethoxysilane (KH-570) at 65°C for 3 hours, with a grafting rate of 20%.
[0026] Inorganic filler: Silica with a particle size of 300 nm and a mass fraction of 15%.
[0027] Initiation system: camphorquinone (CQ) and ethyl-4-dimethylaminobenzoate (4-EDMAB) in a mass ratio of 1:1, with a total mass fraction of 0.5%; dicumyl peroxide (DCP) in a mass fraction of 0.2%.
[0028] Additive: KH-570, mass fraction 1.0%.
[0029] Dentin slurry: Resin matrix: Bisphenol A-glycidyl methacrylate (Bis-GMA) and triethylene dimethacrylate (TEGDMA) in a mass ratio of 1:1.
[0030] Self-healing functional unit: The first self-healing functional unit has a volume fraction of 25% in the resin.
[0031] Inorganic filler: 200 nm particle size silica, with a mass fraction of 20%.
[0032] Initiation system: CQ and 4-EDMAB, mass ratio 1:1, total mass fraction 0.5%; DCP, mass fraction 0.2%.
[0033] Additives: KH-570, 1.0% by mass; tert-butyl peroxide (TBPB), 0.1% by mass.
[0034] Enamelled paste: Resin matrix: UDMA and TEGDMA in a mass ratio of 2:1.
[0035] Self-healing functional unit: The second self-healing functional unit has a volume fraction of 15% in the resin.
[0036] Inorganic filler: Silica with a particle size of 100 nm and a mass fraction of 40%.
[0037] Initiation system: CQ and 4-EDMAB, mass ratio 1:1, total mass fraction 0.5%; DCP, mass fraction 0.2%.
[0038] Additives: KH-570, 1.0% by mass; TBPB, 0.1% by mass.
[0039] First self-healing functional unit: Core component: TEGDMA, accounting for 50% of the microcapsule volume.
[0040] Intermediate trigger layer: Porous silica nanoparticles loaded with benzoyl peroxide (BPO) and N,N-dimethyl-p-toluidine (DMPT) are dispersed in a dilute polymethyl methacrylate (PMMA) solution, accounting for 10% of the microcapsule volume. The BPO loading is 0.35 g / g SiO2, and the DMPT loading is 0.2 g / g SiO2.
[0041] Outer shell: PMMA with a weight-average molecular weight of approximately 150,000, containing 5% by mass of silica nano-damping filler. The average thickness of the shell is 1.8 μm.
[0042] Second self-healing functional unit: Core: Same as the first self-healing functional unit.
[0043] Intermediate trigger layer: Same as the first self-healing functional unit.
[0044] Outer shell: PMMA with a weight-average molecular weight of approximately 150,000. The mass fraction of inorganic nano-damping filler in the shell increases linearly from 5% on the inner surface to 15% on the outer surface. The average thickness of the shell is 2.5 μm.
[0045] Preparation method S1. Preparation of composite microcapsules: Synthesis of PMMA prepolymer: MMA was reacted in tetrahydrofuran with 0.5 wt% AIBN as an initiator and at 60°C under nitrogen protection for 4 hours to obtain a PMMA solution with a weight average molecular weight of approximately 150,000.
[0046] Microfluidic control equipment: The first self-healing functional unit employs a coaxial microfluidic device. The flow rate ratio of the core phase, intermediate phase, and shell phase is 1:2:5. The hydraulic diameter of the channel is 400 μm, and after collection and solidification, microcapsules with a particle size of -80 μm and a wall thickness of 1.8 μm are obtained.
[0047] The second self-healing functional unit employs a three-channel co-current focusing microfluidic device. The core phase is the same as the middle phase. The shell phase is formed by laminar superposition of two PMMA solutions at a 1:1 flow ratio, 25°C, and 0.01 MPa back pressure to create a gradient shell layer. The channel hydraulic diameter is 500 μm, and after collection and solidification, microcapsules with a particle size of -80 μm and a wall thickness of 2.5 μm are obtained.
[0048] S2. Layered preparation and casting: Prepare three layers of slurry according to the above proportions to ensure that each component is evenly dispersed.
[0049] Place the mold on a horizontal platform, inject the base layer slurry in sequence, smooth it with a scraper, and immediately irradiate it with 470 nm blue light for 30 seconds for pre-curing.
[0050] Inject dentin slurry onto the pre-cured base layer, smooth it out, and irradiate with blue light for 30 seconds for pre-curing.
[0051] Finally, inject the enamel slurry, smooth it out, and pre-cure it by irradiating it with blue light for 30 seconds.
[0052] S3. Gradient hot pressing curing and stress control: The mold containing the pre-cured preform is placed in an isostatic pressing cylinder filled with silicone oil. The pressure is increased to 8 MPa at 0.5 MPa / min. Then the temperature is increased to 85°C at 5°C / min and held for 90 minutes. Subsequently, the temperature is decreased to room temperature at 5°C / min, the pressure is released, and the mold is demolded to obtain the final integrated biomimetic multilayer restoration.
[0053] Example 2: The main change in this embodiment is the adjustment of the proportion of the resin comonomer in the base layer to explore its effect on the overall mechanical properties of the material and the interfacial bonding strength with the dentin layer. The preparation steps are basically the same as in Example 1.
[0054] Materials and proportions: Base layer slurry: Resin matrix: The molar ratio of MMA to EMA was adjusted to 8:2. The modification method and grafting rate remained unchanged.
[0055] Inorganic filler: Silica with a particle size of 300 nm and a mass fraction of 15%.
[0056] Initiation system: CQ:4-EDMAB mass ratio of 1:1, total mass fraction 0.5%; DCP mass fraction 0.2%.
[0057] Other additives: KH-570 mass fraction 1.0%.
[0058] Dentin slurry: The formula is the same as in Example 1.
[0059] Enamel layer paste: The formula is the same as in Example 1.
[0060] The first and second self-healing functional units: the materials and specifications are the same as in Example 1.
[0061] Preparation method: S1. Preparation of composite microcapsules: The method and parameters are exactly the same as in Example 1.
[0062] S2. Layered preparation and casting: Prepare three layers of slurry according to the proportions in this embodiment.
[0063] The pouring and layered pre-curing steps are the same as step S2 in Example 1: the base layer, dentin layer, and enamel layer slurry are poured in sequence, and each layer is pre-cured by irradiation with 470 nm blue light for 30 seconds after pouring.
[0064] S3. Gradient hot pressing curing and stress control: Process parameters and operation are the same as in Example 1.
[0065] Expected differences from Example 1: Increasing the MMA ratio increases the rigidity of the base layer resin, and the elastic modulus is slightly higher than that of Example 1 (3.0 ± 0.5 GPa), but the fracture toughness decreases slightly. The solubility parameter deviates slightly from 19.0 (J / cm³). 3 )^0.5 will have a slight effect on the strength of the chemical bonding interface with the dentin layer, which needs to be verified by interlaminar shear strength test.
[0066] Example 3: The main change in this embodiment is to increase the inorganic filler content of the enamel layer, aiming to simulate the characteristics of natural enamel with higher hardness and wear resistance, and to explore its effects on the material's mechanical properties, light curing characteristics and self-healing function triggering efficiency.
[0067] Materials and proportions: Base layer slurry: The formula is the same as in Example 1.
[0068] Dentin slurry: The formula is the same as in Example 1.
[0069] Enamelled paste: Resin matrix: UDMA to TEGDMA mass ratio 2:1.
[0070] Self-healing functional unit: Second self-healing functional unit, volume fraction 15%.
[0071] Inorganic filler: 100 nm particle size silica, with a mass fraction increased to 50%.
[0072] Initiation system: CQ:4-EDMAB mass ratio of 1:1, total mass fraction 0.5%; DCP mass fraction 0.2%.
[0073] Interface additives: KH-570 mass fraction 1.0%, TBPB mass fraction 0.1%.
[0074] The first and second self-healing functional units: the materials and specifications are the same as in Example 1.
[0075] Preparation method: S1. Preparation of composite microcapsules: The method and parameters are exactly the same as in Example 1.
[0076] S2. Layered preparation and casting: Prepare three layers of slurry according to the proportions in this embodiment. When preparing the enamel layer slurry, ensure that the high content of nanofillers is uniformly dispersed and free from agglomeration.
[0077] The pouring and layering pre-curing steps are the same as step S2 in Example 1. Since the viscosity of the enamel layer slurry increases with the increase of filler content, care must be taken to control the flow rate during pouring to ensure a smooth interface.
[0078] S3. Gradient hot pressing curing and stress control: Process parameters and operation are the same as in Example 1.
[0079] Expected differences from Example 1: The hardness and wear resistance of the enamel layer are expected to be significantly improved, but the reduced resin matrix ratio has a certain impact on the encapsulation efficiency of the self-healing microcapsules and the ultrasonic-triggered release efficiency. The solubility parameter changes due to variations in filler content and needs to be re-measured to confirm whether it remains at 19.5 ± 0.3 (J / cm³). 3 Within the range of 0.5, the rheological properties of the slurry and the depth of photocuring will also change.
[0080] Example 4: The main change in this embodiment is that the inorganic nano-damping filler in the self-healing functional unit shell is replaced with silicon carbide instead of silicon dioxide, in order to explore its effect on the mechanical properties of the microcapsule, the ultrasonic trigger threshold and the unexpected rupture rate.
[0081] Materials and proportions: Base layer, dentin layer, and enamel layer slurry: The formula is the same as in Example 1.
[0082] First self-healing functional unit: Core and intermediate trigger layer: Same as in Example 1.
[0083] Outer shell: PMMA uniformly doped with 5% silicon carbide nanoparticles by mass. Target average shell thickness of 1.8 μm.
[0084] Second self-healing functional unit: Core and intermediate trigger layer: Same as in Example 1.
[0085] Outer shell: The mass fraction of silicon carbide nanofiller in the shell increases linearly from 5% on the inner surface to 15% on the outer surface. The target average thickness of the shell is 2.5 μm.
[0086] Preparation method: S1. Preparation of composite microcapsules: The PMMA prepolymer solution was synthesized in the same way as in Example 1.
[0087] Microfluidic control equipment: When preparing the shell-phase prepolymer, silicon carbide nanoparticles are used instead of silicon dioxide. Surface treatment of the silicon carbide is required to ensure its stable dispersion in the PMMA solution.
[0088] The first self-healing functional unit employs a coaxial microfluidic device, with the shell phase being a PMMA solution containing 5 wt% silicon carbide. Channel parameters are fine-tuned based on the slurry's rheological properties to control the wall thickness at 1.8 μm.
[0089] The second self-healing functional unit employs a three-channel co-flow focusing microfluidic device. The shell phase consists of two PMMA solutions superimposed in a laminar flow at a 1:1 flow ratio. By adjusting parameters such as the channel hydraulic diameter, the wall thickness is controlled to be 2.5 μm.
[0090] S2. Layered preparation and casting: The preparation and steps are carried out according to the proportions and steps of Example 1, but the microcapsules used are silicon carbide filler microcapsules prepared in this example.
[0091] S3. Gradient hot pressing curing and stress control: Process parameters and operation are the same as in Example 1.
[0092] Expected differences from Example 1: Silicon carbide has higher hardness and better thermal conductivity. The expected rupture energy density threshold of the microcapsule shell will be approximately 0.1 W / cm² higher than that of a silica system with the same wall thickness. 2 Under the same ultrasonic wave, the local temperature rise is slightly higher, but the unexpected rupture rate is expected to be slightly lower.
[0093] Example 5: This embodiment serves as a comparison, aiming to highlight the importance of the core design of this invention in achieving precise triggering of self-healing and ensuring interlayer bonding strength by eliminating two key design features: the gradient wall-shell structure of the enamel microcapsules and the deliberately introduced chemical bonding interface between the layers.
[0094] Materials and proportions: Base layer slurry: The formula is the same as in Example 1.
[0095] Dentin slurry: The formula is the same as in Example 1.
[0096] Enamelled paste: The resin matrix, inorganic filler with a mass fraction of 40%, and initiation system are the same as in Example 1.
[0097] Self-healing functional unit: The first self-healing functional unit is the same as that of the dentin layer, with a wall shell uniformly doped with 5% silica, eliminating the gradient wall shell design, and has a volume fraction of 15%.
[0098] The deliberate addition of interface additives KH-570 and TBPB has been removed.
[0099] Self-healing functional unit: Only one type of microcapsule was prepared: a uniform shell with a silica filler mass fraction of 5% and a uniform wall thickness of 2.0 μm, for use in the dentin and enamel layers.
[0100] Preparation method: S1. Preparation of composite microcapsules: The PMMA prepolymer solution was synthesized in the same way as in Example 1.
[0101] Microfluidic preparation: Only one type of microcapsule with a wall thickness of 2.0 μm and a uniform shell was prepared. A coaxial microfluidic device was used to adjust parameters such as the hydraulic diameter of the channel to achieve the target wall thickness.
[0102] S2. Layered preparation and casting: The three-layer slurry was prepared according to the proportions described in this embodiment. The same microcapsules were used for both the dentin and enamel layers.
[0103] After each layer is poured, blue light layer pre-curing is still performed, but KH-570 and TBPB are not specifically introduced between the layers to form strong chemical bonds. The main method is to rely on physical stacking and mechanical interlocking generated by light curing shrinkage.
[0104] S3. Gradient hot pressing curing and stress control: Process parameters are the same as in Example 1.
[0105] Expected differences from Example 1: Self-healing performance: The rupture threshold of enamel microcapsules is singular and differs from the optimal design value, making it impossible to achieve priority and precise triggering of repair in cracked areas under complex stress.
[0106] Interface performance: The interlayer bonding depends on physical action. It is expected that the interlayer shear strength will be lower than that of Example 1 after soaking in artificial saliva, and delamination failure is likely to occur.
[0107] Overall performance: In long-term use in a simulated oral environment, the reliability, durability and self-healing efficiency of this control material are expected to be significantly inferior to the experimental materials in Examples 1 to 4.
[0108] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A dental restorative composite material with self-healing function, characterized in that, The device is an integrated biomimetic multilayer structure, comprising a base layer, a dentin layer, and an enamel layer bonded together by chemical bonding interfaces. The base layer resin is a methyl methacrylate-ethyl methacrylate (MMA)-EMA binary copolymer, with a molar ratio of MMA to EMA of 7:
3. The copolymer is modified by grafting with the silane coupling agent γ-methacryloyloxypropyltrimethoxysilane KH-570 at 65±5℃ for 3 hours, achieving a grafting rate of not less than 18%, resulting in a flexural strength of not less than 60 MPa at 23℃ and 50% RH, and an elastic modulus of 3.0±0.5 GPa. The dentin layer resin is a blend of bisphenol A-glycidyl methacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) in a 1:1 mass ratio, with a solubility parameter of 18.2 ± 0.3 (J / cm³). 3 )^0.5; The enamel resin is a blend of urethane dimethacrylate (UDMA) and TEGDMA in a mass ratio of 2:1, with a solubility parameter of 19.5 ± 0.3 (J / cm³). 3 )^0.5; The solubility parameter of the base layer resin is 19.0 ± 0.3 (J / cm³). 3 The solubility parameter is 0.5, and the effect of the inorganic filler added to it on the physicochemical properties of the resin system has been taken into account. The dentin layer contains a first self-healing functional unit, which has a volume fraction of 25±5% in the dentin resin; the enamel layer contains a second self-healing functional unit, which has a volume fraction of 15±5% in the enamel resin. Both the first and second self-healing functional units are composite microcapsules with an overall particle size range of 80±20 μm and a three-layer structure consisting of a core, a shell, and a hull. The inner core contains a liquid repair monomer, wherein the repair monomer is TEGDMA, and the core volume accounts for 50±5% of the total volume of the composite microcapsule; The intermediate trigger layer, accounting for 10±2% of the total volume of the composite microcapsules, is a solid, isolating mixture of benzoyl peroxide (BPO) and N,N-dimethyl-p-toluidine (DMPT). BPO and DMPT are independently loaded onto porous silica nanoparticles (50-200 nm in diameter, 2-5 nm in pore size, and 40±10% porosity) modified by physical adsorption under stirring conditions of 25℃ and 200 rpm. These nanoparticles are modified with 5% KH-550 (by mass) at 60℃ for 2 hours, resulting in a KH-550 grafting rate of at least 10%. The loading amounts are 0.2-0.5 g of BPO and 0.1-0.3 g of DMPT per gram of silica. After accelerated aging in artificial saliva at 37℃ for 6 months, HPLC analysis showed that the contact reaction rate between BPO and DMPT was no higher than 5%. The outer shell is formed by blending polymethyl methacrylate (PMMA) with a weight-average molecular weight of 150,000 ± 20,000 with inorganic nano-damping filler. Its circumferential tensile strength is not less than 15 MPa in artificial saliva medium at 37°C with a loading rate of 1 mm / min. The first self-healing functional unit in the dentin layer has an inorganic nano-damping filler with a mass fraction of 5±1% in its outer shell, which is uniformly distributed, and an average shell thickness of 1.8±0.1 μm. The second self-healing functional unit in the enamel layer has an outer shell with an inorganic nano-damping filler mass fraction that linearly increases from 5% to 15% from the inner surface to the outer surface. The average thickness of the shell is 2.5±0.1 μm. This gradient structure is achieved by a microfluidic device with a three-channel co-flow focusing structure. The shell phase is formed by laminar superposition of two PMMA prepolymers with different filler contents at a flow rate ratio of 1:1 under laminar flow conditions of 25±2℃ and 0.01 MPa back pressure. The minimum energy density threshold required for the shell of the first self-healing functional unit in the dentin layer to fracture is 0.8 ± 0.1 W / cm². 2 The minimum energy density threshold required for the shell of the second self-healing functional unit in the enamel layer to rupture is 1.3 ± 0.1 W / cm². 2 The composite microcapsules are subjected to a frequency f of 40-60 kHz and a power density W of 0.5-2.0 W / cm². 2 When subjected to continuous ultrasonic waves, the repair monomers can preferentially rupture and release in the crack area.
2. The dental restorative composite material with self-healing function according to claim 1, characterized in that, The relationship between the fracture energy density threshold Eth and the average shell thickness d satisfies the formula: Eth = k·d within the range of wall thickness d∈[1.8μm, 2.5μm]. 2 The unit of Eth is W / cm³. 2 d is in μm, and k is a coefficient related to the shell material and structure; When the filler is silica and the PMMA weight-average molecular weight is 150,000 ± 20,000, the k value for the first self-healing functional unit is 0.24 ± 0.02 W·μm. -2 / cm 2 For the second self-healing functional unit, its k value is 0.21 ± 0.02 W·μm. -2 / cm 2 ; When the filler is replaced with silicon carbide, the k value is 0.22 ± 0.02 W·μm. -2 / cm 2 .
3. The dental restorative composite material with self-healing function according to claim 1, characterized in that, The inorganic nano-damping filler is one of silica nanoparticles with a particle size of 50-100 nm and silicon carbide nanoparticles with a particle size of 80-120 nm. When the filler is silica with a mass fraction of 5%, the ultrasonic power density corresponding to shell rupture is 0.8 ± 0.1 W / cm³. 2 Under these conditions, after continuous ultrasonic waves for 60 seconds, the local average temperature rise of the shell was 15±3℃; under simulated chewing cyclic load (frequency 1.5Hz, load force 200 N, 10 cycles)... 6 Under (multiple) conditions, the unexpected rupture rate of the microcapsules was 2 ± 0.5%; When the filler is silica with a mass fraction of 15%, the ultrasonic power density corresponding to shell rupture is 1.3 ± 0.1 W / cm³. 2 Under these conditions, after continuous ultrasonic treatment for 60 seconds, the local average temperature rise was 30±3℃; the unexpected breakage rate was 4.5±0.5%. When the filler is silicon carbide with a mass fraction of 5%, the ultrasonic power density corresponding to shell rupture is 0.9 ± 0.1 W / cm³. 2 Under these conditions, the local average temperature rise after 60 seconds of continuous ultrasonic treatment was 18±3℃, and the unexpected breakage rate was 1.8±0.5%. When the filler is silicon carbide with a mass fraction of 15%, the ultrasonic power density corresponding to shell rupture is 1.4 ± 0.1 W / cm³. 2 Under these conditions, the local average temperature rise after continuous ultrasonic treatment for 60 seconds was 32±3℃, and the unexpected breakage rate was 4.0±0.5%.
4. The dental restorative composite material with self-healing function according to claim 1, characterized in that, The chemically bonded interface comprises a copolymer structure formed by reacting 0.5%-2% of the total mass of the interface resin with γ-methacryloyloxypropyltrimethoxysilane, a silane coupling agent, and 0.1% of the resin mass with tert-butyl peroxide (TBPB). The molar percentage of copolymerizing monomers in the interface region of adjacent resin layers is not less than 40%. The interface is tested on an adhesive sample with dimensions of 2 mm × 2 mm × 25 mm under a loading rate of 1 mm / min. After being immersed in artificial saliva at 37°C for 30 days, the interlaminar shear strength is not less than 15 MPa, 18 MPa, and 22 MPa, respectively.
5. A method for preparing a dental restorative composite material with self-healing function as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Preparation of composite microcapsules: S101. Synthesis of shell-phase PMMA prepolymer: The solution polymerization method was adopted. Methyl methacrylate monomer was dissolved in tetrahydrofuran to form a solution with a mass concentration of 50%. Azobisisobutyronitrile (AIBN) equivalent to 0.5% of the monomer mass was added as an initiator. The reaction was carried out at 60°C under nitrogen protection for 4 hours. The PMMA weight-average molecular weight was controlled within the range of 150,000 ± 20,000 by GPC monitoring. S102. Microfluidic Preparation: Sequential microfluidic technology is employed to control the flow rate ratio of the core phase, intermediate phase, and shell phase at 1:2:
5. The core phase consists of pure TEGDMA monomer; the intermediate phase is a dilute PMMA solution with a solid content of 5% and loaded with porous silica composite particles containing BPO and DMPT; and the shell phase is a mixture of the PMMA solution obtained in step a with a solid content adjusted to 15%-20% and inorganic nano-damping filler, sequentially forming a core-shell-shell three-layer structure. When preparing the second self-healing functional unit for the enamel layer, a three-channel co-current focusing microfluidic device is used. Two shell phase prepolymers with different inorganic nano-damping filler contents (5% and 15%) are laminarly superimposed at a 1:1 flow rate ratio at 25±2℃ and a back pressure of 0.01 MPa to form the shell phase. When preparing the first self-healing functional unit for the dentin layer, a uniform shell phase is used. The shell thickness is precisely controlled by matching the hydraulic diameter of the microfluidic channels. Specifically, when the channel hydraulic diameter is 400±20 mm... When the channel hydraulic diameter is 500±20 μm, microcapsules with a wall thickness of 1.8±0.1 μm and an overall particle size of 80±10 μm are prepared. S2. Layered Preparation and Casting: Separate preparation of the base layer, dentin layer, and enamel layer slurries, with the thickness of each layer controlled within 500 μm; the base layer slurry contains 15% by mass of 300 nm silica inorganic filler, the dentin layer slurry contains 20% by mass of 200 nm silica inorganic filler, and the enamel layer slurry contains 40% by mass of 100 nm silica inorganic filler. The slurry contains nm silica inorganic filler; each layer of the slurry was verified by UV-Vis spectrophotometer to have a blue light penetration depth of ≥500μm at 470nm; each layer of the slurry contains the corresponding proportion of the composite microcapsules, KH-570, and a dual curing initiation system composed of camphorquinone (total mass fraction 0.5%, mass ratio 1:1) and ethyl-4-dimethylaminobenzoate and dicumyl peroxide (mass fraction 0.2%); the slurry is injected into the mold in the order of base layer, dentin layer, and enamel layer, and immediately after each layer is poured, a light is applied at a wavelength of 470nm and an intensity of 100mW / cm. 2 Blue light is irradiated onto the upper surface of the layer for 30 seconds to pre-cure and shape the layers. S3. Gradient hot pressing curing and stress control: The pre-cured mold is placed in an isostatic pressure cylinder filled with silicone oil, and a hydrostatic pressure of 8±0.1 MPa is applied at a rate of 0.5 MPa / min. Then, the temperature is increased to 85℃ at a rate of 5℃ / min. The mold is kept at this temperature for 90 minutes under the condition that the maximum temperature difference inside the mold is ≤±2℃, monitored by a thermocouple inside the mold. Then, the temperature is uniformly reduced to room temperature at a rate of 5℃ / min to complete the final curing. The curing process results in residual stress in the final molded resin matrix ≤3MPa. The hydrostatic pressure suppresses the volume deformation rate of the composite microcapsules at 85℃ from 12±2% under no-pressure conditions to below 6±2%.
